Community-based quit smoking intervention in Sarawak, Malaysia - Md Mizanur, Rahman; Muhammad Siddiq, Daud; Sabrina, Lukas; Kamarudin, Kana; Merikan, Aren; Rudy Ngau, Ajeng; Mohd Faiz, Gahamat (Intelektual Pustaka Media Utama (IPMU), 2022)
Rising worldwide adolescent smoking necessitates national and global research to establish intervention methods. This research evaluated the efficacies of ask, advise, assess, assist, arrange (5A’s) and ask, advise, act (3A’s) interventions. Self-reported quit-smoking attempts were the outcome measure. Six villages were randomly selected and equally divided into three groups: 5A’s, 3A’s, and control (no intervention). There were 519 current participant-smokers aged 13-17 followed-up by phone (first and third months) and face-to-face interviews (sixth and ninth months). Most 3A’s participants (n=12, 7.1%) quitted smoking in the first month, followed by the 5A’s (n=9, 5.3%) and the control (n=3, 1.9%). In the third month, 5A’s participants topped the rank (n=16, 10.7%), followed by the 3A’s (n=14, 9.2%), and control (n=5, 3.4%). As per sixth-month follow-up, the 5A’s group maintained its position on top of the list (n =27, 21.4%), followed by the 3A’s (n=22, 17.1%) and the control (n=5, 4.0%). The majority of 5A’s participants quitted smoking after nine months (n=36, 33.0%), followed by the 3A’s (n=27, 25.5%), while control maintained its position (n=5, 5.0%). Division health officers and school health-teams nationwide should implement them.